2012
DOI: 10.1021/ef300539c
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Oxy-fuel Combustion in an Oxygen Transport Reactor

Abstract: This study aims at investigating the characteristics of oxy-fuel combustion in an oxygen transport reactor (OTR). The cylindrical reactor walls are made of dense, nonporous, mixed-conducting ceramic membranes that only allow for oxygen permeation from the outside air into the combustion chamber. The oxygen permeate mixes with a mixture of CO2 and CH4 (sweep gas) that enters the reactor, resulting in combustion products composed of H2O and CO2. The modeling of the flow process considers a numerical solution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Wang et al [18] has conducted experimental O 2 permeation study in a tubular BSCF membrane and found that for a constant temperature, the O 2 permeation flux is little affected by the feed flow rate. The numerical model studies of Hong et al [39] and BenMansour et al [1] also showed similar behavior. Coming back to our present simulation it appears that there is some effect on the permeated oxygen flux.…”
Section: Oxygen Separation Simulations For Non-reactive and Reactive supporting
confidence: 56%
See 2 more Smart Citations
“…Wang et al [18] has conducted experimental O 2 permeation study in a tubular BSCF membrane and found that for a constant temperature, the O 2 permeation flux is little affected by the feed flow rate. The numerical model studies of Hong et al [39] and BenMansour et al [1] also showed similar behavior. Coming back to our present simulation it appears that there is some effect on the permeated oxygen flux.…”
Section: Oxygen Separation Simulations For Non-reactive and Reactive supporting
confidence: 56%
“…6. It must be mentioned that most of the published papers dealing with OTR have not treated the variation of feed flow rate effect including Ben-Mansour et al [1,2], Hong et al [39] and Habib et al [40]. The reason for this is due to the fact the variation of feed flow rate has very little effect on O 2 permeation in the case of separation only.…”
Section: Oxygen Separation Simulations For Non-reactive and Reactive mentioning
confidence: 99%
See 1 more Smart Citation
“…Their catalytic activity, coupled with oxygen permeation in a controlled manner, enables their use as catalytic membrane reactors with higher product selectivity [2]. Multiple applications have been extensively investigated using typically methane as a feedstock such as; oxidative coupling [7][8][9][10]; partial oxidation [5,6,11]; and oxy-fuel combustion [12][13][14][15][16]. In spite of these promising applications, the operating regimes, in which fuel conversion and oxygen permeation are predominantly attributed to catalytic or/and gas-phase reactions, have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results from these two studies have elucidated that fuel oxidation reactions and their chemical kinetic rates have substantial influences on oxygen permeation, their models considered a simple well-stirred reactor which does not resolve the state near the surface. Ben-Mansour et al [13], Habib et al [14] and Nemitallah et al [15,16] modeled two dimensional reactors and considered the local thermodynamic state to evaluate the permeation rate, but assumed one-or two-step global reactions without examining the coupling of homogeneous and heterogeneous chemistry to minimize computational costs. Wang and Lin [20] and Tan et al [12] assumed the kinetic parameters of perovskite membranes, but they ignored homogeneous-phase reactions that may take place at the temperature considered in their study.…”
Section: Introductionmentioning
confidence: 99%